Beds or bonds? Conditional solidarity in the coronavirus crisis; Betten oder Bonds? Konditionale Solidarität in der Corona-Krise - Sebastian Koos; Dirk Leuffen (University of Konstanz, Cluster of Excellence "The Politics of Inequality", Das Progressive Zentrum e.V., 2020)
The coronavirus crisis exacerbates inequality in the European Union. It gives rise to a critical debate about the future of Europe concerning a key question: In what way does the project of integration require a higher degree of European solidarity? To what extent are Europeans willing to help each other, and what kind of help are they willing to provide? The results from a recent survey of the German residential population, presented in this paper, offer a mixed picture: Whereas people strongly support medical solidarity, their willingness to support fi nancial redistribution is limited. As a consequence, it will be crucial to use ideational leadership to activate the potential for solidarity towards a united, viable Europe marked by limited inequality—especially with the German Council Presidency commencing on July 1st, 2020. – – Die Corona-Krise verschärft die Ungleichheit in der Europäischen Union (EU). Sie regt eine Debatte um die Zukunft Europas in einer zentralen Frage kritisch an: Inwiefern bedarf das Integrationsprojekt einer verstärkten innereuropäischen Solidarität? Wieviel und welche Art von Hilfe sind die EuropäerInnen bereit, wechselseitig zu leisten? Die hier vorgestellten Ergebnisse einer Umfrage unter der deutschen Wohnbevölkerung zeichnen ein gemischtes Bild: Während die Bereitschaft zu medizinischer Solidarität hoch ist, zeigt sich nur eine begrenzte Bereitschaft zur Unterstützung fi nanzieller Umverteilungsmaßnahmen. Dementsprechend gilt es, die Solidaritätspotentiale für ein geeintes, zukunftsfähiges Europa mit begrenzter Ungleichheit durch ideational leadership zu mobilisieren – insbesondere mit Blick auf die deutsche EU-Ratspräsidentschaft, die am 1. Juli 2020 beginnt.
urn:nbn:de:bsz:352-2-1cqravs329vzk5
Keywords: 320